From Prosody to Rhythm: Modelling the Structure of Karakkereng in the Bugis Massureq Tradition as Humanistic Intelligence - Rahmat Kurniawan; Sri Riski Wulandari; Muh. Kurniawan Adi K.W Adi K.W (Fakultas Sastra - Universitas Muslim Indonesia, 2026)
Massureq, the Bugis oral epic-chanting tradition of South Sulawesi, integrates the prosodic organisation of the I La Galigo text with Karakkereng, a cyclical percussive structure that shapes performance time. This study models the correspondence between linguistic prosody and Karakkereng rhythm and considers its implications for humanistic intelligence and culturally responsive digital preservation. Using a mixed-method ethnomusicological case-study design, the research combined participant observation, interviews, and acoustic analysis in Praat of twelve excerpts from the Sawerigading Opunna Ware episode, performed by Itangang, an authoritative passure’ from Barru Regency. Three systematic correspondence rules were identified. First, vowels lasting at least 0.30 seconds corresponded to doubled or dotted beat values in 78% of syllable-beat pairs. Second, syllables with fundamental-frequency prominence of 28–45% above the performer’s mean received the primary metric accent in 81% of cases. Third, inter-clausal pauses of at least 300 milliseconds consistently marked the beginning of a new uleng-uleng rhythmic cycle, yielding 100% reliability within the corpus. The co-occurrence of vowel lengthening and high F0 prominence produced mappellong, a fully accented strike observed in 94% of relevant cases. These findings demonstrate that Karakkereng is not an independent musical accompaniment but an audible realisation of Classical Bugis prosodic structure. The resulting model gives empirical form to humanistic intelligence by showing how phonological knowledge, rhythmic competence, and embodied performance are inseparable in Massureq practice. It also provides a foundation for phonetically annotated archival corpora, culturally sensitive AI-assisted retrieval, and apprenticeship-oriented performance assessment. Further multi-performer research is needed to test its broader transferability.